Pengaruh Trust In A Brand, Product Diversification Dan Word Of Mouth Terhadap Keputusan Nasabah Membeli Produk Wealth Management BNI Kanwil Manado - Pandeirot, Inneke Jelly (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The purpose of this research is to know the influence of Trust In A Brand, Product Diversification And Word Of Mouth Against To Customer Buying Decisions BNI Wealth Management Products.(BNI Emerald Product). This type of research is type of associative research using multiple linier regression data analysis. The results showed that partially and simultaneously Trust in a Brand, Product Diversification and Word of Mouth have a significant effect on Buying Decision Wealth Management Bank BNI Kanwil Manado product.Keywords: Trust In A Brand, Product Diversification, Word Of Mouth, Buying DecisionÂ